Evaluation of different solvents and solubility parameters on the morphology and diameter of electrospun pullulan nanofibers for curcumin entrapment. (1st January 2021) - Guerrini, Lilia M.; Oliveira, Maurício P.; Stapait, Camila C.; Maric, Milan; Santos, Amilton M.; Demarquette, Nicole R.
Highlights: Effect of different solvents on the morphology of electrospun Pull was evaluated. Pull nanofibers was produced with water, DMF and their mixtures (30 wt.% of DMSO). The best solvents with the smallest fiber diameter was DMF/DMSO (70/30 wt.%). The entrapment of curcumin in the Pull nanofibers was efficient. The results obtained created new approaches applications for drug delivery systems. Abstract: In this work, the effect of different solvents and solvent binary mixtures on the morphology of electrospun pullulan (Pull) nanofibers was evaluated. The solution viscosities, interactions between solvent and polymer, as well as, solvent vapor pressure, were correlated to the morphology and diameters of the nanofibers. Water, dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) and Teas graphs that rely on the use of Hildebrand solubility parameters were used to identify the most suitable mixtures of solvents. The best binary mixture of solvents to produce Pull nanofibers without defects and with small diameters (203±32 nm) was DMF/DMSO in the ratio of 70/30 wt.%. Pull nanofibers containing 3 and 5 wt. % of curcumin (Curc) in a mixture of DMF/DMSO (70/30 wt.%) were then obtained, and the entrapment efficiency was evaluated using 1 H NMR and a UV-–vis spectrophotometer. The results obtained in this work create a new approach for the production of Pull nanofibers for drug delivery systems.